Mastering Advanced Qualitative Research Methods in Social Studies - Qolamani, Khalid Ilias Basheer (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study delves into the intricate domain of advanced qualitative research methods in social studies, highlighting their growing significance in studying multifaceted social phenomena. The paper offers a comprehensive overview of foundational principles and core techniques required for rigorous qualitative investigation, encompassing varied research designs such as ethnography, grounded theory, and narrative inquiry. Techniques for data collection, including in-depth interviews, focus groups, and participant observation, are explored, along with strategies ensuring research quality, such as validity, reflexivity, and triangulation. Analytical methods, from coding to thematic analysis, are discussed, with an emphasis on the utilization of software tools. The article underscores the ethical imperatives of the qualitative research process, addresses challenges like subjectivity and generalizability, and points toward emerging trends, including digital qualitative research and interdisciplinary approaches. In conclusion, it asserts that mastering qualitative methods demands a profound commitment to reflective and ethical practices, ensuring rich insights into human experiences for social studies scholarship.